Assessment of the newborn prenatally exposed to drugs: The history. Issue 2 (April 2019) - Kaltenbach, Karol
Abstract: This paper reviews the history of the development of scoring tools used to assess the occurrence and severity of the Neonatal Abstinence Syndrome. Beginning with the first tools published in 1975, this review describes tools published through 2010; identifies each tool's strengths and weaknesses; and discusses their representation in the literature.